2009
DOI: 10.4103/0250-474x.56023
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial evaluation of mangiferin analogues

Abstract: The naturally occurring xanthone glycoside mangiferin has been isolated by column chromatography from the ethanol extract of stem bark of Mangifera indica. Mangiferin was further converted to 5-(N-phenylaminomethyleno)mangiferin, 5-(N-p-chlorophenylaminomethyleno) mangiferin, 5-(N-2-methylphenylaminomethyleno) mangiferin, 5-(N-p-methoxyphenylaminomethyleno) mangiferin, 5-(N, N-diphenylaminomethyleno) mangiferin, 5-(N--napthylaminomethyleno) mangiferin and 5-(N-4-methylphenylaminomethyleno) mangiferin. Mangifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 10 publications
2
17
0
3
Order By: Relevance
“…1). Mangiferin has been reported to possess biological activities against oxidation [1], bacteria [2], tumor [3], al- lergy [4], human immunodeficiency virus [5], neurodegradation [6], and hyperlipidemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…1). Mangiferin has been reported to possess biological activities against oxidation [1], bacteria [2], tumor [3], al- lergy [4], human immunodeficiency virus [5], neurodegradation [6], and hyperlipidemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2009) registraram atividade antimicrobiana do composto mangerin, isolado de caule, e seus anĂĄ-logos sintĂ©ticos frente Ă s espĂ©cies Staphylococcus aureus, Escherichia coli e Aspergillus niger. Esses mesmos autores apontam que o anĂĄlogo sintĂ©tico de mangerin, 5-(N-α-napthylaminomethyleno), inibiu o crescimento da espĂ©cie C. albicans, entre tanto nĂŁo foi testado a CIM.…”
Section: Discussionunclassified
“…Compounds 1-3 are polyphenols from natural origins that play important bioactive roles, such as being an antioxidant for compounds 1-3 [14], being antimicrobial [17] and having anti-inflammatory [14,18] and vasorelaxant [16] properties for compound 3. Previous reports have indicated that there is evidence supporting the correlation between the phenolic contents in plant extracts and their bioactivity properties.…”
Section: Thermal Degradation Kinetics Of Compounds 1-3 In Dried Ae Anmentioning
confidence: 99%
“…It has been noted that the plant extracts that exhibit significant antioxidant capabilities have good potential as antimicrobials [19]. Several phenolic compounds, such as luteolin, myricetin [20] and compound 3 [17], showed antibacterial activity. To understand the appropriate conditions for maintaining the quality of the plant extract to ensure a high level of phenolic contents and their activities, the kinetic model was used to establish and control the plant extract quality.…”
Section: Thermal Degradation Kinetics Of Compounds 1-3 In Dried Ae Anmentioning
confidence: 99%